The impact of the COVID-19 pandemic on socio-economic conditions for households in Jambi city, Indonesia - Junaidi, Junaidi; Suandi, Suandi; Perdana, Silvia Mawari (Humanities, Arts and Social Sciences Studies, 2022)
The COVID-19 pandemic is the biggest shock the world has experienced, Indonesia in particular. This pandemic has had various negative impacts on both the health and socio-economic sectors. This study analyzes the impact of the COVID-19 pandemic on socio-economic conditions as well as household food security and analyzes families’ economic coping strategies during the COVID-19 pandemic in Jambi City. The primary data comes from household surveys in Jambi City. This research uses a quantitative-qualitative approach with descriptive methods. The quantitative approach uses descriptive statistical tools. A qualitative approach is used to analyze the in-depth interview results. The research results found that the COVID-19 pandemic has had a negative impact on various areas of people’s lives, including economic, social, cultural, and religious domains, as well as food security. 13.27 percent of the 196 household heads lost their job. Furthermore, 8.67 percent were compelled to change jobs/businesses to lower-paying ones. Almost a third (31.93 percent) of those still working have had their working hours reduced, and nearly three-quarters (74.27 percent) have had their income reduced by 34.48 percent. Regarding socio-cultural and religious aspects, 76.75 percent stated that they try to cut down on numerous daily activities. 68.37 percent of households have an energy consumption deficiency based on food security, while 46.43 percent have a protein consumption shortfall. On the other hand, households mostly cut back expenses rather than generating more income as their economic coping strategy. This strategy decreases the quality of life in the community. As a result, a government policy that provides direct cash assistance to affected households to maintain their quality of life is required. Community groups should handle the assistance to purchase nutritious food items and enhance household food security. Furthermore, the government can provide business capital support to those who have lost their employment, followed by company management assistance so that the established firms can operate effectively.